ANALISIS IMPLIKASI KONSEP KODRAT ALAM DAN TRIPUSAT PENDIDIKAN KI HAJAR DEWANTARA DI SD TUNAS LESTARI SUNGAI BASUNG: ANALISIS IMPLIKASI KONSEP KODRAT ALAM DAN TRIPUSAT PENDIDIKAN KI HAJAR DEWANTARA DI SD TUNAS LESTARI SUNGAI BASUNG - Asep Awaludin; Fina Febriyanti; Trisiani; Waryanto; Soedjono (STKIP Subang, 2024)
This research aims to analyze the implications of implementing the concept of Natural Nature and Ki Hajar Dewantara's Tricenter of Education at SD Tunas Lestari Sungai Basung. The main focus of the research is to explore how Ki Hajar Dewantara's educational principles are implemented in the context of modern education in rural elementary schools. Using a qualitative approach with a case study method, this research involved direct observation, in-depth interviews with teachers and school principals, as well as analysis of school documents. Data was collected over a three-month period to obtain a comprehensive picture of educational practices at the school. The results of the research show that SD Tunas Lestari Sungai Basung has attempted to integrate the concept of Nature in its curriculum and teaching methods, with an emphasis on learning that is appropriate to students' natural development. The implementation of the Education Tricenter can be seen through increasing the involvement of parents and the community in the education process. The main challenges identified include limited resources and the need to adapt the concept to the local context. Nevertheless, this research found a positive impact on student character development and increased learning motivation. In conclusion, the application of the Ki Hajar Dewantara concept at Tunas Lestari Sungai Basung Elementary School shows significant potential in improving the quality of education, although it still requires further adjustments and development. This research provides valuable insight into how traditional educational principles can be revitalized in the modern education system in Indonesia. Keywords: Ki Hajar Dewantara, Nature of Nature, Tricenter of Education, Basic Education, Case Study